A Novel CRAd in Combination With Cisplatin Enhanced the Antitumor Efficacy in Ovarian Cancer. Issue 9 (1st November 2011) - Zhang, Bei; Liu, Yaowu; Zhang, Peiying; Wei, Yaqin; Yin, Xiaoxing; Zheng, Junnian
Abstract : Objectives: The aim of this study was to investigate the combined effects of a novel survivin promoter-based conditionally replicating adenovirus (CRAd-S.RGD) plus cis -diamminedichloroplatinum (cisplatin, CDDP) in ovarian cancer in vitro and in vivo. Methods: The viability of human ovarian cancer cell line SKOV3 was determined by MTT assay following the infection with different doses of CRAd-S.RGD, either alone or in combination with CDDP. The antitumor efficacies and survival curves were evaluated at the end of the treatment regimens with the subcutaneous administration of CRAd-S.RGD, CDDP, combined therapy of CRAd-S.RGD plus CDDP, or phosphate-buffered saline in a SKOV3 xenograft animal model. Furthermore, the apoptosis rate of tumor tissues in mice was determined subsequent to the treatments. Results: In vitro, the CRAd-S.RGD destroyed SKOV3 cells by oncolysis in a dose-dependent manner, and the viability of SKOV3 cells was significantly lower in the combined-therapy group than that in the individual-therapy groups. In vivo, enhanced tumor inhibition and animal survival rates were obtained in a synergistic manner with CRAd-S.RGD plus CDDP, as compared with the treatment with CRAd-S.RGD or CDDP alone. There was an increase in the apoptosis rate of the cells following the combined therapy. The results clearly demonstrated that there was a synergistic effect in the combination of CRAd-S.RGD and CDDP in increased therapeutic efficacy. Similar therapeutic efficacy could be obtained with CRAd-S.RGD plus CDDP at 2 lower doses that minimized the drug toxicity to host tissues. Conclusions: The strategy of CRAd-S.RGD in combination with CDDP was a potential therapeutic modality for the therapy in ovarian cancer. Abbreviations: CDDP - cisplatin, cis -diamminedichloroplatinum, CRAd - conditionally replicating adenovirus, CRAd-survivin - the survivin promoter-based conditionally replicating adenovirus, CRAd-S.RGD - CRAd–survivin-RGD4C, MOI - multiplicity of infection, PBS - phosphate-buffered saline, PI - propidium iodide